Dose-Volume Analysis of Radiation-Induced Optic Neuropathy After Single-Fraction Stereotactic Radiosurgery. Issue 4 (4th June 2014) - Pollock, Bruce E.; Link, Michael J.; Leavitt, Jacqueline A.; Stafford, Scott L.
Abstract: BACKGROUND: The risk of radiation-induced optic neuropathy (RION) is the primary limitation of single-fraction stereotactic radiosurgery (SRS) for many patients with parasellar lesions. OBJECTIVE: To define the normal tissue complication probability of the anterior visual pathways (AVPs) after single-fraction SRS. METHODS: Retrospective review comparing visual function before and after SRS in 133 patients (266 sides) with pituitary adenomas having SRS between October 2007 and July 2012. Patients with prior radiation therapy or SRS were excluded. The median follow-up after SRS was 32 months. RESULTS: The median maximum point dose to the AVP was 9.2 Gy (interquartile range [IQR], 6.9-10.8). One hundred seventy-four sides (65%) received >8 Gy: the median 8-Gy volume was 15.8 mm 3 (IQR, 3.7-36.2). Ninety-four sides (35%) received >10 Gy; the median 10-Gy volume was 1.6 mm 3 (IQR, 0.5-5.3). Twenty-nine sides (11%) received >12 Gy; the median 12-Gy volume was 0.1 mm 3 (IQR, 0.1-0.6). No patient had a RION after SRS. The chances of developing a RION at the 8-Gy, 10-Gy, and 12-Gy volumes (95% confidence interval) in this series were 0% to 2.6%, 0% to 4.7%, and 0% to 13.9%, respectively. CONCLUSION: The AVP in patients without prior radiation treatments can safely receive radiation doses up to 12 Gy with a low risk of RION. Although additional studies are needed to better delineate the normal tissue complication probability of the AVP, adherence to the AVP radiation tolerance guidelines developed 20 years ago (8 Gy) limits the applicability and potentially the effectiveness of single-fraction SRS for patients with lesions in the parasellar region.